Persepsi dan Sikap Masyarakat tentang Pengobatan Tradisional (Studi Kasus di RT 06 Desa Wae Ajang, Kecamatan Satar Mese, Kabupaten Manggarai) - Oktavianus Randu; Lenny Sofia Bire Manoe; Balkis Soraya Tanof (Jurnal Pluralis, 2024)
The people of RT 06 Wae Ajang Village are tending to choose the traditional medicinesystem, because they thought that traditional medicine have many benefits. Besides that,the people of RT 06 Wae Ajang Village also thought that traditional medicine is moreeffective than modern medicine because basically there are diseases that could not curedwith modern medicine and it is cheaper to have traditional treatment.